Analisis kelayakan lahan budi daya rumput laut (Ulva sp.) pada lokasi rencana pengembangan North Sulawesi Marine Education Center di Likupang Timur - Edy, Selvanus; Ngangi, Edwin L. A.; Mudeng, Joppy D. (e-Journal BUDIDAYA PERAIRAN, 2017)
The purpose of this research was to know and evaluate the condition of aquatic environment and water quality parameters for cultivation of seaweed Ulva sp. This research was conducted on North Sulawesi Marine Education Center (NSMEC). NSMEC is planned to be built at Marine Field Station FPIK UNSRAT located in Likupang Timur Kabupaten Minahasa Utara. The waters of NSMEC development area are geographically located at 1040.437 'LU and 12504.499' BT. The determination of 4 stations was done by purposive sampling which was considered to represent the condition of waters. Coordinate stations were recorded with GPS help. The data were collected for 14 days every 6:00 pm, at 12:00 pm and 17:00 pm. The observation of environmental conditions was carried out for protection factor and substrate of water base, while water quality parameter measured in situ included depth, brightness, temperature, dissolved oxygen (DO) salinity, pH and current velocity. Phosphate, nitrate and total suspended solid (TSS) were measured. Tide measurements were measured every hour for 24 hours. Data analysis used conformity matrices that included scores and weights for the determination of conformity classes. Class suitability was used to describe the suitability of seaweed. The results showed that the waters of the NSMEC development zone were in class S1 meaning very suitable for seaweed cultivation location. The analysis results of each station found that 4 stations were very suitable. As conclusion, water environment and water quality parameters of the waters of North Sulawesi Marine Education Center development area located at Marine Field Station FPIK UNSRAT were categorized as very suitable for seaweed cultivation, Ulva sp.Keywords: Ulva sp., feasibility analysis, water quality, location suitability